Pendampingan Perangkat Desa Puloniti Dalam Perencanaan ‎Kegiatan Fisik Dana Desa ‎ - Sarasanty, Diah; Tri Asmorowati, Erna; Nizar Zulfika, Dicki (Indra Institute Research & Publication, 2023)
Expansion of infrastructure through the allocation of village funds to improve urban services is increasingly happening in all regions. Every year, the allocation of village funds through the APBN continues to increase. Allocation of village funds needs to be supported by proper preparation of proposals, including files that need to be completed. The understanding of village officials in the initial situation analysis shows that there is a lack of understanding in planning infrastructure activities, so there is a need for increased skills in reading and understanding technical drawings, making drawings with AutoCAD software tools, and calculating the volume of work. The fulfillment of technical drawings for village infrastructure work shows an increase in the capacity of Puloniti village officials in planning technical drawings using AutoCAD, complete with work volume calculations.